2022
DOI: 10.1177/16878132221106577
|View full text |Cite
|
Sign up to set email alerts
|

Numerical thermal featuring in γAl2O3-C2H6O2 nanofluid under the influence of thermal radiation and convective heat condition by inducing novel effects of effective Prandtl number model (EPNM)

Abstract: The investigation of thermal transport in the nanofluid attained much interest of the researchers due to their extensive applications in automobile, mechanical engineering, radiators, aerodynamics, and many other industries. Therefore, a nanofluid model is developed for γAl2O3-C2H6O2 by incorporating the novel effects of Effective Prandtl Number Model (EPNM), thermal radiations, and convective heat condition. The model discussed numerically and furnished the results against the governing flow quantities. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 31 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Bilal et al (2022) explored the impact of heat radiation on liquid motion over a linear stretched surface and explained that with elevation in porosity and radiation factors, there is a growth in skin friction. Adnan (2022) discussed numerically the effects of radiative and convective thermal conduction on nanoliquid flow on a non-linear extended sheet and determined that fluid motion weakened with growth in the radiation factor, which, on the other hand, augmented both the Nusselt number and skin friction. Yaseen et al (2022) discussed motion of hybrid nanoparticles amid two plates placed in parallel direction with the influence of the Darcy permeable medium and heat radiations effects and concluded that the Nusselt number augmented with progression in radiation and porosity factors.…”
Section: Introductionmentioning
confidence: 99%
“…Bilal et al (2022) explored the impact of heat radiation on liquid motion over a linear stretched surface and explained that with elevation in porosity and radiation factors, there is a growth in skin friction. Adnan (2022) discussed numerically the effects of radiative and convective thermal conduction on nanoliquid flow on a non-linear extended sheet and determined that fluid motion weakened with growth in the radiation factor, which, on the other hand, augmented both the Nusselt number and skin friction. Yaseen et al (2022) discussed motion of hybrid nanoparticles amid two plates placed in parallel direction with the influence of the Darcy permeable medium and heat radiations effects and concluded that the Nusselt number augmented with progression in radiation and porosity factors.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, as the magnetic field increases, the boundary layer's thickness decreases. Future applications of the fifth-order Runge-Kutta shooting technique could include a range of physical and technological difficulties (Adnan et al, 2021;Adnan, 2022;Adnan and Ashraf, 2022;Khan et al, 2022a;Khan et al, 2022b). According to (Jamshed et al, 2021b;Jamshed, 2021;, there have been several recent advancements that explore the importance of the research domain under consideration.…”
Section: Discussionmentioning
confidence: 99%
“…The acquired model is then treated through numerical means and implemented RK technique (see Refs. 33 35 ) successfully. The complete detailed implementation process of RK method 36 , 37 is described in the below flow diagram (see Figure 2 ).…”
Section: Mathematical Investigationmentioning
confidence: 95%